Rise of the legend [videorecording (DVD)] - Chow, Roy Hin Yeung; Hung, Samo, 1952-; Peng, Yuyan, 1982-; Wang, Luodan, 1984- (Well Go USA Entertainment, 2016)
In nineteenth-century China, Huang Feihong returns to the town where his father was murdered to face off against a ruthless crime boss.